Cattle production practices and the incidence of dark cutting beef. (November 2019) - Mahmood, S.; Dixon, W.T.; Bruce, H.L.
Abstract: The effects of cattle sex, production system, growth promotant use, slaughter season, carcass phenotype, and pre-slaughter cattle management on the incidence of beef carcasses grading Canada B4 (dark cutting) were investigated using two data sets (A, n = 2009, and B, n = 86, 408) containing data from cattle that produced Canada Prime, AAA, AA, A, and B4 carcasses. The probability of producing a Canada B4 carcass was greater ( P < .0001) for heifers than steers in both data sets, with the likelihood of dark cutting decreasing with increased carcass weight in heifers in data set B. The incidence of dark cutting was increased ( P < .0001) in Winter-born calf-fed (WC) and Fall-born calf-fed (FC) heifers. Production system and phenotype appear to interact to influence the incidence of dark cutting. Highlights: Rearing systems of cattle influence the likelihood of dark cutting beef Heifers are more susceptible to cutting dark than steers Moderate growth implant use does not influence the incidence of dark cutting Slow growing cattle are predisposed to dark cutting Delayed slaughter can escalate dark cutting incidence in heifers